Analysis of Decreased Motivation and Interest in Online Learning for Islamic Religious Education in Elementary Schools - Qurnia A'yuni; Rahmad Salahuddin (Indonesian Journal of Islamic Studies, 2022)
The pandemic Covid-19 has forced all activities to be carried out at home. This is very influential in the world of education. The students’ motivation and interest in learning decreases. The research intends to explore information related to the causes of decreased student motivation and interest in online learning Islamic religious education at SD Muhammadiyah 11 Randegan. The research method is qualitative with a phenomenological approach. The data were analyzed qualitative using the Miles Huberman analysis model. The data was proved from the result of the research that the decline in students’ motivation and interest in online learning Islamic religious education at SD Muhammadiyah 11 Randegan occurs slowly. Meanwhile, the causes of the decline in students’ motivation and interest in online learning in Islamic religious education at SD Muhammdiyah 11 Randegan are boring learning, limited learning media used online, lack of direct teacher supervision, lack of parental attention to students when learning online, more students prefer playing mobile phones instead of online learning, and limited interaction between students.